Rethinking Coordination of Services to Refugees in Urban Areas Managing the Crisis in Jordan and Lebanon - Culbertson, Shelly (RAND Corporation, 2016)
This study analyzes coordination of international and national entities managing the Syrian refugee response in urban areas in Jordan and Lebanon and provides recommendations on improving coordination strategies and practices. It presents a new framework for planning, evaluating, and managing refugee crises in urban settings, both in the Syrian refugee crisis as well as other such situations going forward.